2011
DOI: 10.1007/s11434-011-4802-7
|View full text |Cite
|
Sign up to set email alerts
|

A vacuole localized β-glucosidase contributes to drought tolerance in Arabidopsis

Abstract: The phytohormone abscisic acid (ABA) plays a critical role in plant growth, development, and adaptation to various stress conditions. The cellular ABA level is constantly adjusted to respond to changing physiological and environmental conditions. To date, the mechanisms for fine-tuning ABA levels remain elusive. Here, we report that BGLU10, a member of a multigene family of β-glucosidases, contributes to drought tolerance in Arabidopsis. The T-DNA insertion mutant bglu10 exhibited a droughtsensitive phenotype,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…Whether Os9BGlu31 and similar vacuolar TG can act to modulate these responses by transfer of glucose from other 1-O-acyl ␤-D-glucose esters remains to be investigated, but its transfer of glucose to and from the carboxyl groups on the auxins indole acetic acid, naphthalene acetic acid, and 2,4-D, GA 4 , and ABA is intriguing. In fact, AtBGlu10, which falls in the same phylogenetic cluster at Os9BGlu31, has recently been suggested to act in 1-O-ABA glucosyl ester metabolism and as an 1-O-acyl glucose-dependent anthocyanin TG (47,48). The induction of the Os9BGlu31 gene under the stress conditions of drought, ABA, ethephon, methyl jasmonate, 2,4-D, and kinetin is at least consistent with Os9BGlu31 involvement in adaptation to changes in the environment.…”
Section: Discussionmentioning
confidence: 68%
“…Whether Os9BGlu31 and similar vacuolar TG can act to modulate these responses by transfer of glucose from other 1-O-acyl ␤-D-glucose esters remains to be investigated, but its transfer of glucose to and from the carboxyl groups on the auxins indole acetic acid, naphthalene acetic acid, and 2,4-D, GA 4 , and ABA is intriguing. In fact, AtBGlu10, which falls in the same phylogenetic cluster at Os9BGlu31, has recently been suggested to act in 1-O-ABA glucosyl ester metabolism and as an 1-O-acyl glucose-dependent anthocyanin TG (47,48). The induction of the Os9BGlu31 gene under the stress conditions of drought, ABA, ethephon, methyl jasmonate, 2,4-D, and kinetin is at least consistent with Os9BGlu31 involvement in adaptation to changes in the environment.…”
Section: Discussionmentioning
confidence: 68%
“…This finding raised the question of whether vacuolar ABA-GE also has an important function as an ABA reservoir. This hypothesis was supported by recent identifications of two vacuolar b-glucosidases that hydrolyze vacuolar ABA-GE (Wang et al, 2011;Xu et al, 2013). The vacuolar AtBG1 homolog AtBG2 forms high molecular weight complexes, which are present at low levels under normal conditions but significantly accumulate under dehydration stress.…”
mentioning
confidence: 74%
“…increased drought tolerance). The other identified vacuolar ABA-GE glucosidase, BGLU10, exhibits comparable mutant phenotypes to AtBG2 (Wang et al, 2011). This redundancy may explain the less pronounced mutant phenotypes of vacuolar ABA-GE glucosidases compared with the ER-localized AtBG1.…”
mentioning
confidence: 85%
“…Beta-glucosidases participate in lignification of the cell walls, b-glucan catabolism, activation of phytohormones, stimulation of the aromatic compounds synthesis and in other defensive processes (Cairns and Esen 2010). In response to drought stress, bglucosidases may increase the amount of abscisic acid (ABA)-an essential signaling factor which is involved in adapting plants to stress conditions (Bargmann and Munnik 2006;Cairns and Esen 2010;Wang et al 2011). Studies on b-glucosidase showed its important role in increasing the tolerance of plants to osmotic and drought stress (Hermosa et al 2011;Wang et al 2011).…”
Section: Discussionmentioning
confidence: 99%